Bacterial Infections, DNA Virus Infections, and RNA Virus Infections Manifest Differently in Neutrophil Receptor Expression - Esa-Matti Lilius; Jari Nuutila (The Scientific World Journal)
Treating viral illnesses or noninfective causes of inflammation with antibiotics is ineffective and contributes to the development of antibiotic resistance, toxicity, and allergic reactions, leading to increasing medical costs. A major factor behind unnecessary use of antibiotics is, of course, incorrect diagnosis. For this reason, timely and accurate information on whether the infection is bacterial in origin would be highly beneficial. In this paper we will present our recent studies on the expression of opsonin receptors on phagocytes. The analysis of the expression levels of FcγRI, CR1, and CR3, along with CRP and ESR data, provides a novel application to the diagnosis of infectious and inflammatory diseases. The best clinical benefit will be obtained when the individual variables are combined to generate the CIS point method for a bacterial infection marker, DNAVS point for differentiating between DNA and RNA virus infections, and CRP/CD11b ratio for a marker of Gram-positive sepsis.